Effect of cyclic loading by force of chewing and higher pressure on the surface of metal-ceramic and press-ceramic endocrowns - Makeev, V.; Skalskyy, V.; Pavlychko, R. (Actual Dentistry, 2018)
Introduction: choosing material of choice for endocrowns by studying their stability and wear under cyclic loading. Materials and Methods. Performing mechanical tests for cyclic loading chewing pressure force of 450 and 750 N to pressed ceramic dental materials (IPS e.max Press) and metal (GC Initial MC) in VUSM 500 using the method of acoustic emission (AE) and systems SKOP-8M. Enveloping craks in the scanning electron microscope (SEM) ZEISS EVO 40XVP and further data processing by statistical methods. Results. Pressceramics fatigue fracture occurred in stages too deep to form mikrokratera in material with smooth edges,that actively developed after 360 thousand loading cycles. In PFM gradually individual layers of ceramic coating (cleavage facet) exfoliated and cracks appeared locally in areas likely location microdefects after 125 thousand loading cycles. Conclusions. Under the influence of cyclic loading (500 thousand cycles), all dental materials were fatigued. The best performance showed the press ceramic because this type of material without additional fused ceramic can be recommended for the endocrowns in situation of pathological conditions by abrasion. Key words: endocrowns, pressed ceramic, metal ceramics, cyclic loading, acoustic emission.